Supporting Chronic Pain Management across Provincial and Territorial Health Systems in Canada: Findings from Two Stakeholder Dialogues - Michael G Wilson; John N Lavis; Moriah E Ellen (Pain Research and Management)
BACKGROUND: Chronic pain is a serious health problem given its prevalence, associated disability, impact on quality of life and the costs associated with the extensive use of health care services by individuals living with it.